2012
DOI: 10.3846/bme.2012.01
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Asset Classes Through the Business Cycle

Abstract: This study was driven by the dissimilar performance characteristics displayed by asset classes over the business cycle. The authors aim to explore assets classes on the grounds of a scientific literature review and a statistical analysis. Business cycles are divided into four stages to explore broad movements in returns of asset classes and a possible existence of asymmetrical effects of determinants within stages. Six main asset classes were analysed: US stocks, EAFE stocks, Bonds, Gold, Real Estate and Commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Like Dzikevičius and Vetrov (2012a), it seeks to take advantage of the movements of the economic cycle, to increase the performance of a portfolio and contrary to what was found by Han, Li & Yin (2018), where the economic cycles studied through the CLI do not fully reflect the real conditions of the stock markets.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Like Dzikevičius and Vetrov (2012a), it seeks to take advantage of the movements of the economic cycle, to increase the performance of a portfolio and contrary to what was found by Han, Li & Yin (2018), where the economic cycles studied through the CLI do not fully reflect the real conditions of the stock markets.…”
Section: Resultsmentioning
confidence: 94%
“…They found that this indicator could anticipate the movements of the economic cycle, and thus modify the weightings of the stocks and achieve better return/risk efficiency in the portfolio. In another study these authors (Dzikevičius & Vetrov, 2012a) included other financial assets to verify that the OECD indicator could provide information on return expectations. They found that asset classes behave in a different way along the OECD business cycle, showing that the CLI can provide significant information on financial market expectations.…”
Section: Introductionmentioning
confidence: 99%
“…Guessing of the future business cycle is very complicated. When the eco nomy is at its recession, neither its duration nor its severity are known; moreover, the effects of a crisis are different in different sectors of the economy, which makes the assess ment of a country's economic situation even more difficult (Dzikevičius, Vetrov 2012).…”
Section: Concept Of a Business Cyclementioning
confidence: 99%
“…Allocation in each of these asset classes needs to be a well-educated decision. Dzikevicius and Vetrov (2012) combined business cycle and asset allocation theories by adding valuable information about performance of asset classes during different phases of the business cycle and demonstrated that different asset classes have different return/risk characteristics over the business cycle. They thus demonstrated how business cycle approach can be used for decision making.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different asset classes perform differently at different points of time. The performance is affected by the business cycle (Dzikevicius & Vetrov, 2012) as well as other local and global macroeconomic parameters. Crude oil, real estate, gold etc.…”
Section: Introductionmentioning
confidence: 99%